Topical Application of Adelmidrol + Trans-Traumatic Acid Enhances Skin Wound Healing in a Streptozotocin-Induced Diabetic Mouse Model - Siracusa, Rosalba; Impellizzeri, Daniela; Cordaro, Marika; Gugliandolo, Enrico; Peritore, Alessio F.; Di Paola, Rosanna; Cuzzocrea, Salvatore (Frontiers in Pharmacology, 2018)
Impaired wound healing is considered to be one of the severe complications associated with diabetes. Adelmidrol and Trans-traumatic acid are commonly called Nevamast®. This gel consists precisely of 2% Adelmidrol and 1% Trans-traumatic acid. Thanks to its components, it is capable of favoring the natural process of skin re-epithelialization. This study testes the theory that topical usage of Adelmidrol+Trans-traumatic acid has important effects on the healing and closure of diabetic wounds in a streptozotocin-induced diabetic mouse model. Diabetes was induced by intra-peritoneal injection of Streptozotocin (STZ; 60 mg/kg) in 0.01M citrate buffer (pH 4.5) administrated for 5 consecutive days. After diabetes induction, two longitudinal incisions were done on the dorsum of the mice. The animals were killed between 6 and 12 days from wound-induction. We found that mice with diabetes presented compared to mice under our control: a retarded wound closure, characterized by an important reduction in the levels of transforming growth factor-β, plus an important increase of vascular endothelial growth factor and endothelial-type nitric oxide synthase expression, together with a reduction of adhesion molecules such as intercellular adhesion molecule-1 and P-selectin and a prolonged elevation of the levels of matrix metalloproteinase-9 and matrix metalloproteinase-2 in wound tissues. This study demonstrates that topical application of Adelmidrol+Trans-traumatic acid has important effects on the healing and closure of diabetic wounds in an STZ-induced diabetic mouse model.